The Effect Of Lactobacillus Paracasei Isolated From Yoghurt On The Growth And Production Of Staphylococcus Aureus Enterotoxin - Mahnoosh Parsaeimehr (پیاورد سلامت, 2014)
Background and Aim: Probiotics are useful bacteria which, after being consumed, leave useful effects on human health. The present study was conducted to examine the antimicrobial effect of Lactobacillus paracasei on pathogenic bacteria, especially on Staphylococcus aureus in the field of food microbiology. Materials and Methods: In this study, the effect of Lactobacillus paracasei isolated from yoghurt (1×108 cfu/ml) on the growth of Staphylococcus aureus (1×105 cfu/ml) was assessed at two different temperatures of 25 °C and 35°C in TSB. Then, samples from cocultures and control were pour plated in Baird Parker agar and MRS agar to compute the number of S. aureus and Lactobacillus paracasei at 0, 24, 48, 72 hours after incubation. Then, enterotoxin production was evaluated by ELIZA rida screen kit. The data were investigated by ANOVA and K-square (chi-square) tests.  Results: It was found that compared to controls, Lactobacillus paracasei inhibited the growth of Staphylococcus aureus and reduced the number of S. aureus cells about 3 logs in 25°C and 2 logs in 35°C. The production of A, C, and E enterotoxins was inhibited by S. aureus at a temperature of 25°C according to ELIZA rida screen test. The figure was 35°C for enterotoxins E and A.  Conclusion: Probiotics can be used as a new approach for the biocontrol of S. aureus without using antibiotics.